Production of Permanent Magnets from Recycled NdFeB Powder with Powder Extrusion Moulding - Stefan Rathfelder; Stephan Schuschnigg; Christian Kukla; Clemens Holzer; Carlo Burkhardt (Journal of Manufacturing and Materials Processing, 2024)
In the last fifteen years, several groups have investigated metal injection moulding (MIM) of NdFeB powder to produce isotropic or anisotropic rare earth magnets of greater geometric complexity than that achieved by the conventional pressing and sintering approach. However, due to the powder’s high affinity for oxygen and carbon uptake, sufficient remanence and coercivity remains difficult. This article presents a novel approach to producing NdFeB magnets from recycled material using Powder Extrusion Moulding (PEM) in a continuous process. The process route uses powder obtained from recycling rare earth magnets through Hydrogen Processing of Magnetic Scrap (HPMS). This article presents the results of tailored powder processing, the production of mouldable feedstock based on a special binder system, and moulding with PEM to produce green and sintered parts. The magnetic properties and microstructures of debinded and sintered samples are presented and discussed, focusing on the influence of filling ratio and challenging processing conditions on interstitial content as well as density and magnetic properties.